A case of a gastric granular cell tumor preoperatively diagnosed and successfully treated by single-incision laparoscopic surgery - Atsushi Yasuda; Takushi Yasuda; Haruhiko Imamoto; Yoko Hiraki; Kohta Momose; Hiroaki Kato; Mitsuru Iwama; Osamu Shiraishi; Masayuki Shinkai; Motohiro Imano; Yutaka Kimura (Surgical Case Reports)
Abstract Background Granular cell tumors (GCT) in the gastrointestinal tract are rare. Herein, we describe a case of a gastric GCT diagnosed preoperatively by endoscopic ultrasound-guided fine needle aspiration biopsy (EUS-FNAB) and successfully resected by single-incision laparoscopic surgery (SILS). Case presentation A 46-year-old Japanese woman had a tumor located in the angle of the stomach that was approximately 1.5 cm in diameter. Abdominal computed tomography (CT) revealed a submucosal tumor (SMT), which was finally diagnosed as a gastric GCT using EUS-FNAB. The tumor was not identified by CT 1 year and 4 months before diagnosis; therefore, because there was a possibility that the tumor was malignant, we performed surgical wedge resection using SILS. The patient had an uneventful recovery postoperatively and was discharged without complications 3 days after surgery. The tumor was pathologically diagnosed as a benign GCT that remained within the muscular layer. No recurrence or complications have occurred in the first 16 months since the surgery. Conclusion Because gastric GCTs are generally benign and are rarely associated with lymph node metastasis, SILS seems to be a safe and feasible surgical approach for treating GCTs.